1995
DOI: 10.1111/j.1476-5381.1995.tb13240.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation by 5‐hydroxytryptamine2B receptors of endothelium‐dependent relaxation in rat jugular vein

Abstract: 1 An 'atypical' 5-HT2 receptor which is located on the endothelium of rat jugular vein has been described. In the present study we 4 These data are consistent with the presence of 5-HT2B receptors mediating endothelium-dependent relaxation of rat jugular vein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 12 publications
4
56
0
Order By: Relevance
“…Mastomys carcinoid tumor primary cultures, clonal neural-like 1C11* /5HT serotonergic cells and 5-HT 2B receptor transfected LM6 fibroblasts, the 5-HT 2 receptor agonist DOI (or 5-HT, data not shown) always triggers intracellular cGMP accumulation resulting from both cNOS and iNOS activation. Such a link between 5-HT and NO could already be suspected in view of the simultaneous involvement of these two agents in smooth muscle contractility (6,30), vascular contraction (7,31), and related migraine pathogenesis (32). Because 5-HT 2B receptors are present in stomach, intestine, pulmonary smooth muscles, kidney, as well as in myocardium, vascular endothelium, and meningeal tissues (3,33,34), they are obvious candidates to trigger the NO response associated to 5-HT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mastomys carcinoid tumor primary cultures, clonal neural-like 1C11* /5HT serotonergic cells and 5-HT 2B receptor transfected LM6 fibroblasts, the 5-HT 2 receptor agonist DOI (or 5-HT, data not shown) always triggers intracellular cGMP accumulation resulting from both cNOS and iNOS activation. Such a link between 5-HT and NO could already be suspected in view of the simultaneous involvement of these two agents in smooth muscle contractility (6,30), vascular contraction (7,31), and related migraine pathogenesis (32). Because 5-HT 2B receptors are present in stomach, intestine, pulmonary smooth muscles, kidney, as well as in myocardium, vascular endothelium, and meningeal tissues (3,33,34), they are obvious candidates to trigger the NO response associated to 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, the receptor couples with PIP 2 hydrolysis, similarly to the two other members (5-HT 2A and 5-HT 2C ) of the 5-HT 2 receptor family. In contrast, the 5-HT 2B receptor stimulation fails to stimulate PIP 2 hydrolysis in rat fundus (6) and in rat vasculature (7). Signaling processes involving 5-HT 2B receptors and distinct from PIP 2 hydrolysis might thus occur.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It has previously been suggested that endothelial 5-HT2c receptors mediate 5-HT-induced relaxation in porcine pulmonary artery (Glusa & Richter, 1993) and rat jugular vein (Bodelsson et al, 1993), but ketanserin (1 gM) failed to cause antagonism, which is inconsistent with its submicromolar affinity for 5-HT2c receptors and leaves open the possibility of mediation through 5-HT2B receptors. Ellis et al (1995) have indeed recently suggested that endothelium-dependent relaxation of rat jugular vein by 5-HT is mediated through 5-HT2B…”
Section: Effects Of Skandf 103829mentioning
confidence: 97%
“…In other vascular beds, 5-HT can induce endothelium-dependent vasodilation via the 5-HT 2C receptor (Bodelson et al, 1993), the 5-HT 2B receptor (Glusa & Roos, 1996;Ellis et al, 1995) and the 5-HT 1D/1B receptor (Gupta, 1992). There is also evidence that 5-HT can mediate vasodilation directly through 5-HT 4 and 5-HT 7 receptors located on vascular smooth muscle (Cocks & Arnold, 1992;Leung et al, 1996;Terron, 1996).…”
Section: Introductionmentioning
confidence: 99%